The Sandman. Vol. 8, World's end - Gaiman, Neil (DC Vertigo, 2019)
"Improbably caught in a June blizzard, two wayward compatriots stumble upon a mysterious inn and learn that they are in the middle of a 'reality storm.' Now surrounded by a menagerie of people and creatures from different times and realities, the two stranded travelers are entertained by mesmerizing myths of infamous sea creatures, dreaming cities, ancient kings, astonishing funeral rituals, and moralistic hangmen"--